Magnetic structure and field dependence of the cycloid phase mediating the spin reorientation transition in Ca_{3}Ru_{2}O_{7} - Q. Faure; C. D. Dashwood; C. V. Colin; R. D. Johnson; E. Ressouche; G. B. G. Stenning; J. Spratt; D. F. McMorrow; R. S. Perry (Physical Review Research, 2023)
We report a comprehensive experimental investigation of the magnetic structure of the cycloidal phase in Ca_{3}Ru_{2}O_{7}, which mediates the spin reorientation transition and establishes its magnetic phase diagram. In zero applied field, single-crystal neutron diffraction data confirm the scenario deduced from an earlier resonant x-ray scattering study: For 46.7K <T< 49.0 K the magnetic moments form a cycloid in the a-b plane with a propagation wave vector of (δ,0,1) with δ≃0.025 and an ordered moment of about 1μ_{B}, with the eccentricity of the cycloid evolving with temperature. In an applied magnetic field applied parallel to the b axis, the intensity of the (δ,0,1) satellite peaks decreases continuously up to about μ_{0}H≃5T, above which field the system becomes field polarized. Both the eccentricity of the cycloid and the wave vector increase with field, the latter suggesting an enhancement of the antisymmetric Dzyaloshinskii-Moriya interaction over the symmetric exchange interactions via magnetostriction effects. Transitions between the various low-temperature magnetic phases have been carefully mapped out using magnetometry and resistivity. The resulting phase diagram reveals that the cycloid phase exists in a temperature window that expands rapidly with increasing field, before transitioning to a polarized paramagnetic state at 5 T. High-field magnetoresistance measurements show that below T≃70K the resistivity increases continuously with decreasing temperature, indicating the inherent insulating nature at low temperatures of our high-quality, untwinned, single crystals. We discuss our results with reference to previous reports of the magnetic phase diagram of Ca_{3}Ru_{2}O_{7} that utilized samples which were more metallic and/or polydomain.